2014
DOI: 10.1007/s10549-014-2944-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial of melatonin on breast cancer survivors: impact on sleep, mood, and hot flashes

Abstract: Purpose To examine the effects of melatonin supplementation on sleep, mood, and hot flashes in postmenopausal breast cancer survivors. Methods In a randomized, double-blind, placebo-controlled study, 95 postmenopausal women with a prior history of stage 0-III breast cancer who had completed active cancer treatment (including hormonal therapy) were randomly assigned 1:1 to either 3 mg oral melatonin (n=48) or placebo daily (n=47) for 4 months. Sleep, mood, and hot flashes were assessed at baseline and four mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 34 publications
(48 reference statements)
4
81
0
1
Order By: Relevance
“…tance of longitudinal studies because analyzing the patient in 2 or more stages of treatment and documenting the difference in quality of sleep, may be helpful to nurses in managing their patients care. Nine articles reported randomized clinical trials [8,10,[16][17][18][19][20][21]] and 3 were a secondary analysis [4,[22][23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…tance of longitudinal studies because analyzing the patient in 2 or more stages of treatment and documenting the difference in quality of sleep, may be helpful to nurses in managing their patients care. Nine articles reported randomized clinical trials [8,10,[16][17][18][19][20][21]] and 3 were a secondary analysis [4,[22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Because the sleep disturbances are common among breast cancer survivors, even after completion of active cancer treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 95 postmenopausal women with a prior history of stage 0-III breast cancer and who had completed active cancer treatment, 3 mg of melatonin or placebo was used for 4 months. Subjects receiving melatonin experienced significantly greater improvements in subjective sleep quality but there were no significant differences in measures of depression or hot flashes, presumably because of the low amounts of melatonin used [171] ( Table 2). …”
Section: Levels Of Amt6s In 12-h Overnight Urine Samplesmentioning
confidence: 99%
“…However, they generally remained underdiagnosed and poorly treated [170][171][172][173]. In a cross-sectional survey study on nearly 1,000 cancer patients to examine the prevalence of sleep problems, sleep disturbance was most prevalent among the lung and breast cancer patients.…”
Section: Clinical Application Of Melatonin In Cancermentioning
confidence: 99%
“…(6) Depression and mood swings may present throughout treatment or even after its conclusion. (7,8) Depressive symptoms are predictors of subjective sleep quality in women with breast cancer before, during and after radiation therapy. (9) Other authors have found that women with early-stage breast cancer when compared with a control group including women without breast cancer, showed a worsening in sleep quality, higher depressive symptoms, more fatigue, and lesser quality of life, one year after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%